Colombia Between The Local and The Global: Regional Insertion Within The New Global Economy - Lampis, Andrea; Kiku Rodríguez, Laura (Sociedad y Economía, 2012)
The issue of regional divergence in the face of a global economy has been analyzed in Colombia mostly from the perspective of economics. On the basis of indicators from the geographical regions of the country, this research analyses four main feature that shape local-global dynamics within Colombian regions: institutional and structural transformations, demography, quality of life and geographical changes. The integrated analysis of data on population, spatial concentration, quality of life, migration patterns, decentralization and productive structure poses a number of questions concerning the asymmetries of the benefits related to regional inclusion to more competitive markets.